One-Sided Weakness Admitted with Hypokalemic Periodic Paralysis - Yaman, Fatih Nazmi; Sahan, Mustafa; Yilmaz, Mustafa (Derman Medical Publ, 2014)
Hypokalemic periodic paralysis (HPP) is a genetic disorder that characterized by recurrent attacks of skeletal muscle weakness with associated hypokalemia which is precipitated by hypotermia, stress, infection, carbonhydrate load, glucose infusion, metabolic alkalosis, general anesthesia, steroids and licorice root. 52-year-old male patient while working in a cold enviroment, began to complain of weakness in the arms and legs. The patient was brought to the emergency department due to the continuation of weakness complaints in the left arm and leg. The neurological examination had 5/5 strength in the upper-right and lowerright extremities, 3/5 strength in the upper-left and lower-left extremities. Serum electrolytes: Potassium: 2.7 mEq/L, 1.9 mEq/L control. There was no evidence of bleeding and infarction in Computerized Brain Tomography and Brain MR. After intravenous infusion of potassium, at the third hour the patient's neurological symptoms resolved completely, patient was mobilized. In this case we present one-sided weakness admitted to the emergency department, the diagnosis of patient with HPP. We aimed to emphasize that this diagnosis should be keeping in mind that among the causes paralysis and delayed diagnose and treatment may be mortal in HPP.
Keywords: Hypokalemia; Periodic Paralysis; One-Sided Weakness